(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This work aimed to make a brief analysis of the aspects related to the contextualization of the flexibilization of labor rules in Brazilian Labor Law and the impacts of the current scenario implanted by the pandemic of the new coronavirus that haunts and plagues Brazil and the world. The historical analysis shows that the work has undergone changes in its composition requiring a specific social and labor legislation – Labor Law, which today sees the need to adjust to the new requirements, in order to preserve the issues related to the relationships between employer and the current legal security, in this scenario, it is evident the flexibility of the labor rules, especially, in this face of the present state of public calamity and, although, precarious and provisional, an exception of removal of the workers, in a way to allow the reduction of wages and working hours.